Unionizing Delivery Platform Workers. The Spatiality of Struggles over Regulation and Deregulation of Delivery Work in Spain - López-García, Irene; Ribón-Seisdedos, Maria Antonia; Morales-Muñoz, Karol; Roca, Beltrán (Relations industrielles / Industrial Relations, 2023)
AbstractThis article is about recent changes in the union strategy of Spanish platform workers. Using a socio-spatial approach to labour processes and disputes, we first describe the context of union organizing: how the business model of delivery platforms has evolved and how it is regulated in Spain. We then analyze the first initiatives to organize couriers in Spain. These initiatives can be classified under the heading of community unionism and have focused on specific spaces of union activism (state regulation and community support). Next, we explore how their newly won employee status has caused couriers to adopt more conventional forms of union organizing and focus on other spaces. Finally, we discuss the main challenges of reconciling union models with the working world of delivery platforms.Summary This article is about recent changes in the union strategy of Spanish platform couriers. Using a socio-spatial approach to labour processes and disputes, we first describe the context of union organizing: how the business model of delivery platforms has evolved and how it is regulated in Spain. We then use qualitative interviews with union delegates, document analysis and participant observation to analyze the first initiatives to organize couriers in Spain by the network Couriers for Rights (Riders por Derechos). These initiatives can be classified under the heading of community unionism and have focused on specific spaces of union activism (state regulation and community support). Next, we explore how their newly won employee status has caused couriers to adopt more conventional forms of union organizing and, consequently, focus on other spaces of activism (mainly firms and workplaces). Finally, we discuss the main challenges of reconciling the different ways of unionizing couriers in a new context characterized by technology-driven deregulation and fragmentation of work, by growing demand for digital worker rights and by the existence of professional associations in which couriers defend themselves as independent contractors rather than as employees.